Interaction, instruments and performance: HCI and the design of future music technologies - Chamberlain, Alan; Pestova, Xenia; Bødker, Mads; Kallionpää, Maria; De Roure, David; Benford, Steve (2017)
Rationale There has been little chance for researchers, performers and designers in the UK to come together in order to explore the use and design of new and evolving technologies for performance. This workshop examines the interplay between people, musical instruments, performance and technology. Now, more than ever technology is enabling us to augment the body, develop new ways to play and perform, and augment existing instruments that can span the physical and digital realms. By bringing together performers, artists, designers and researchers we aim to develop new understandings how we might design new performance technologies.